Two patients with Papillon–Lefèvre syndrome without periodontal involvement of the permanent dentition. Issue 4 (13th February 2021) - Umlauft, Julian; Schnabl, Dagmar; Blunder, Stefan; Moosbrugger‐Martinz, Verena; Kapferer‐Seebacher, Ines; Zschocke, Johannes; Schmuth, Matthias; Gruber, Robert
Abstract: Papillon–Lefèvre syndrome (PLS) is a rare autosomal recessive genodermatosis characterized by palmoplantar keratoderma and severe periodontitis leading to premature loss of primary and permanent teeth. PLS is caused by loss‐of‐function mutations in CTSC, lacking functional cathepsin C, which impairs the activation of neutrophil serine proteases. Precise pathogenesis of periodontal damage is unknown. Patient 1 presented with well‐demarcated, transgredient, diffuse, palmoplantar keratoderma and psoriasiform lesions from the age of 2 years. Based on severe and recurrent periodontal inflammation, his dentist had diagnosed PLS at the age of 3 years and provided a strict oral hygiene regimen with repeated adjunct antibiotic therapies. Oral acitretin 10 mg/day along with tretinoin ointment at the age of 9 greatly improved palmoplantar keratoderma. Aged 18 years, the patient exhibited an intact permanent dentition and absence of periodontal disease. Patient 2, a 30‐year‐old man, suffered from transgredient, diffuse, palmoplantar keratoderma with fissuring from the age of 2 months, marked psoriasiform plaques on elbows and knees, and nail dystrophy. Intriguingly, without specific dental treatment, teeth and dental records were unremarkable. He was referred with a suspected diagnosis of psoriasis. Both patients were otherwise healthy, blood tests and sonography of internal organs were within normal limits. Panel sequencing revealed loss‐of‐function mutations in CTSC, c.322A>T (p.Lys108Ter) and c.504C>G (p.Tyr168Ter) in patient 1 and homozygous c.415G>T (p.Gly139Ter) in patient 2. The final diagnosis of unusual PLS was made. PLS should be considered in palmoplantar keratoderma lacking periodontitis or tooth loss.